Analysis and Implementation of Improved Software Phase-Locked Loop for Single-phase Grid-connected Inverter. Issue 1 (March 2020) - Zhou, Defang; Fang, Yu; Cao, Songyin; Yao, Yong
Abstract: For single-phase grid connected inverter, based on the traditional closed-loop structure of three-phase phase-locked loop (PLL), an improved software PLL was proposed. The basic principle of the phase-locked loop was analyzed and its mathematical model was deduced. In addition, the software implementation method of the phase-locked loop was presented. Then, the influence resulted from the change of amplitude, frequency and phase on the grid voltage was simulated with PSIM software. The results show that the software phase-locked loop can realize the phase tracking at any time in the cycle effectively and quickly, without waiting for the zero crossing of the grid. Finally, the software phase-locked loop proposed in this paper was implemented respectively by using TI's DSP TMS320F28035 and TMS320F2808 and applied to the 500W dual-channel single-phase grid-connected micro-inverter and 5kW single-phase grid-connected inverter. The simulation and experiment results verify the proposed software phase-locked loop.